2012
DOI: 10.1143/jjap.51.06fj09
|View full text |Cite
|
Sign up to set email alerts
|

Effective Linewidth Measurement of 45-nm-Half-Pitch Ultraviolet Nanoimprint Lithography Patterns by Scanning Electron Microscope Inspection and Extremely Shallow Si Etching

Abstract: Resist pattern shrinkage during a scanning electron microscope (SEM) inspection is a critical issue in the measurement of the linewidth or critical dimension (CD) of sub-100 nm polymer patterns. For example, the pattern shrinkages were set to 2.3–4.4 nm for half-pitch (hp) 45–90 nm line and space (L/S) PAK-01 patterns fabricated by UV nanoimprint under SEM conditions to diminish pattern shrinkage. We propose an evaluation method of actual CDs of UV nanoimprint lithography (UV-NIL) patterns by extremely shallow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…We have demonstrated that the rapid bubble-free filling of mold pattern cavities with dimensions ranging from several tens of nanometers (45-nm half-pitch) to several hundreds of micrometers can be accomplished using PFP as the environmental gas in UV-NIL and PAK-01 resins (Toyo Gosei) [18][19][20][21]. Not only is using a PFP atmosphere a potential means to achieve quick and bubble-free cavity filling, but its use is also beneficial as it decreases the viscosity of the UV-curable resin [19], decreases the amount of resin that sticks to the mold during demolding [20], and lowers the demolding forces to approximately onethird of that when performed in air [21]. However, the global warming potential (GWP) 1030 of PFP may prevent its industrial use because of environmental concerns.…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that the rapid bubble-free filling of mold pattern cavities with dimensions ranging from several tens of nanometers (45-nm half-pitch) to several hundreds of micrometers can be accomplished using PFP as the environmental gas in UV-NIL and PAK-01 resins (Toyo Gosei) [18][19][20][21]. Not only is using a PFP atmosphere a potential means to achieve quick and bubble-free cavity filling, but its use is also beneficial as it decreases the viscosity of the UV-curable resin [19], decreases the amount of resin that sticks to the mold during demolding [20], and lowers the demolding forces to approximately onethird of that when performed in air [21]. However, the global warming potential (GWP) 1030 of PFP may prevent its industrial use because of environmental concerns.…”
Section: Introductionmentioning
confidence: 99%
“…UV-nanoimprinted patterns were transferred onto Si by the linewidth evaluation method using extremely shallow Si etching combined with residual layer removal etching. 27) The measured RLT was approximately 20 nm. The etching conditions were as follows: both SF 6 and O 2 gas flow rates of 10 sccm, a chamber pressure of 1.3 Pa, and an RF power of 100 W. The etching time was 15 s, which corresponds to the Si etched depth of approximately 15 nm.…”
Section: Pattern Transfer To Evaluate Difference In Width Of Two-step...mentioning
confidence: 94%